In vivo soft tissue compressive properties of the human hand. - Victoria Spartacus; Maedeh Shojaeizadeh; Vincent Raffault; James Shoults; Ken Van Wieren; Carolyn J Sparrey (PLoS ONE)
Background/purpose Falls onto outstretched hands are the second most common sports injury and one of the leading causes of upper extremity injury. Injury risk and severity depends on forces being transmitted through the palmar surface to the upper extremity. Although the magnitude and distribution of forces depend on the soft tissue response of the palm, the in vivo properties of palmar tissue have not been characterized. The purpose of this study was to characterize the large deformation palmar soft tissue properties. Methods In vivo dynamic indentations were conducted on 15 young adults (21-29 years) to quantify the soft tissue characteristics of over the trapezium. The effects of loading rate, joint position, tissue thickness and sex on soft tissue responses were assessed. Results Energy absorbed by the soft tissue and peak force were affected by loading rate and joint angle. Energy absorbed was 1.7-2.8 times higher and the peak force was 2-2.75 times higher at high rate loading than quasistatic rates. Males had greater energy absorbed than females but not at all wrist positions. Damping characteristics were the highest in the group with the thickest soft tissue while damping characteristics were the lowest in group with the thinnest soft tissues. Conclusion Palmar tissue response changes with joint position, loading rate, sex, and tissue thickness. Accurately capturing these tissue responses is important for developing effective simulations of fall and injury biomechanics and assessing the effectiveness of injury prevention strategies.